2016
DOI: 10.1159/000443355
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Clostridium difficile</i></b> Infection: A Model for Disruption of the Gut Microbiota Equilibrium

Abstract: The gut microbiota is a complex ecosystem defined by the combination of microorganisms living in the gastrointestinal tract. Its equilibrium is intimately involved in several aspects of vital process for human physiology and nutrition. Its composition changes depending on both exogenous and endogenous factors. The disruption of the gut microbiota by antibiotics often leads to an opportunistic infection by Clostridium difficile. The unbalanced intestinal microbiota promotes spore germination, growth of vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The biological framework provided by the large cohort studies by Imhann et al and Jackson et al and the cross‐over trial by Freedberg et al shows partial taxonomic overlap between the microbiota of PPI users and those observed in C difficile infection. These include reduced alpha diversity, increased abundance of the class Gammaproteobacteria, the family Enterobacteriaceae and the genera Veillonella , Enterococcus , Streptococcus and Lactobacillus , along with decrease in the families Ruminococcaceae and Lachnospiraceae and the genus Bifidobacterium . Freedberg et al also identified a significant increase in KEGG pathways corresponding to Staphylococcus aureus infection and to bacterial invasion of epithelial cells, including genes for antibacterial peptides and for maintenance of epithelial integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The biological framework provided by the large cohort studies by Imhann et al and Jackson et al and the cross‐over trial by Freedberg et al shows partial taxonomic overlap between the microbiota of PPI users and those observed in C difficile infection. These include reduced alpha diversity, increased abundance of the class Gammaproteobacteria, the family Enterobacteriaceae and the genera Veillonella , Enterococcus , Streptococcus and Lactobacillus , along with decrease in the families Ruminococcaceae and Lachnospiraceae and the genus Bifidobacterium . Freedberg et al also identified a significant increase in KEGG pathways corresponding to Staphylococcus aureus infection and to bacterial invasion of epithelial cells, including genes for antibacterial peptides and for maintenance of epithelial integrity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clearance of hepatitis B virus infection requires the reestablishment of the gut microbiota. Drugs also affect the microbiome including the drugs used to treat DM2 [77]. But also in the opposite direction.…”
Section: Gut Microbiota and Diabetes Typementioning
confidence: 99%
“…It may be assumed that the bowel is the primary site of clostridial colonization which may predispose C. difficile to spread by translocation or intestinal perforation [17] , [42] . Indeed, monomicrobial CDB was present as frequently as CDB associated with additional pathogens to C. difficile (30/60, [50%]), which is similar to the 50% (6/12) of Lee et al series, even if it has been reported that CDB were rather polymicrobial infections probably because of the small number of cases recorded at that time [27] , [43] , [44] , [45] .…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Severe underlying diseases are also commonly mentioned as predisposing situations to CDI developing. Any factors that disturb the host-microbiota homeostasis can promote C. difficile colonization and infection [11] , [12] , [13] , [14] , [15] , [16] , [17] . The most commonly incriminated antimicrobials are cephalosporins and fluoroquinolones but all antimicrobial classes are associated with a risk of CDI and the antimicrobial stewardship programmes may play a key role in CDI prevention [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%